Corporate Value: Persona pada Company Profile PT. Kereta Api Indonesia - Muhammad, Alfitra Maharindra; Prawiradiredja, Sanhari; Fitriyah, Irmia (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2018)
Kereta Api Indonesia is a train state-owned holding(BUMN). They create meaning by company profile video using Youtube. Companny profile is a business that explain the companny thoroughly. What is meant is the companys value as well as the value of the products. Researches will also discuss about the content of the video and also provide a detailed discussion in this study. This research uses qualitative method, that is by analytical descriptive method by looking at video recording companny profile of Kereta Api Indonesia.Keywords: companny profile, train, corporate value